Meta-analysis of efficacy and safety of pembrolizumab for the treatment of advanced or recurrent cervical cancer - Xue Zhang; Wen-Jie Yin; Ai-Li Zhang; Xiao-Xiao Zhang; Li-Juan Ding; Jiao Zhang; Shu-Ting He; Jie-Ping Yan (Journal of Obstetrics and Gynaecology)
Background This meta-analysis seeks to assess the efficacy and safety of pembrolizumab in individuals with advanced or recurrent cervical cancer.Methods Databases from PubMed, Embase, and the Cochrane Library were all thoroughly searched for pertinent research. Outcomes include complete response (CR), partial response (PR), stable disease (SD), disease progression (PD), overall response rate (ORR), disease control rate (DCR), median progression-free survival (mPFS), median overall survival (mOS), and adverse events (AEs) were retrieved for further analysis.Results Ten trials with 721 patients were included in this meta-analysis. The pooled results for patients with cervical cancer receiving pembrolizumab were as follows: CR (0.06, 95%CI: 0.02–0.10), PR (0.15, 95%CI: 0.08–0.22), SD (0.16, 95%CI: 0.13–0.20), PD (0.50, 95%CI: 0.25–0.75), ORR (0.26, 95%CI: 0.11–0.41) and DCR (0.42, 95%CI: 0.13–0.71), respectively. Regarding survival analysis, the pooled mPFS and mOS were 3.81 and 10.15 months. Subgroup analysis showed that pembrolizumab in combination was more beneficial in CR (0.16 vs. 0.03, p = 0.012), PR (0.24 vs. 0.08, p = 0.032), SD (0.11 vs. 0.19, p = 0.043), ORR (0.42 vs. 0.11, p = 0.014), and mPFS (5.54 months vs. 2.27 months, p < 0.001) than as single agent. The three most common AEs were diarrhoea (0.25), anaemia (0.25), and nausea (0.21), and the incidence of grade 3–5 AEs was significantly lower, rarely surpassing 0.10.Conclusions For patients with advanced or recurrent cervical cancer, this systematic review and meta-analysis demonstrated that pembrolizumab had a favourable efficacy and tolerability. Future research will primarily focus on optimising customised regiments that optimally integrate pembrolizumab into new therapies and combination strategies. Designed to maximise patient benefit and efficiently control adverse effects while maintaining a high standard of living.